(untitled) (World Bulletin of Social Sciences, 2024)
Innovation in healthcare organizations plays a key role in driving improvement, improving the patient experience, and solving complex challenges in the healthcare industry. This extensive article will explore the key factors influencing innovation in healthcare organizations, explore methods to encourage innovative practices, and highlight specific strategies to promote a culture of innovation in healthcare settings